Developing our financial markets to finance the energy transition - Madungandaba, Gcebile F. (University of the Witwatersrand, Johannesburg, 2023)
Developing a financial market is complex and tedious; therefore, the needs of various stakeholders must be considered, and market efficiency must be ensured to develop the renewable energy (RE) market effectively. This study offers valuable guidance on the effective allocation of capital resources in the renewable energy (RE) market to facilitate a smooth transition to renewable energy. To achieve this aim, panel data from 42 developing nations in Africa, Asia, and South America, spanning 1990-2019, are analysed. This study uses a panel fixed effects model to investigate the relationship between renewable energy production and credit, equity, and bond market development. The results of the empirical analysis suggest that all three dimensions of financial development, namely credit, equity, and bond, are positively associated with renewable energy production, albeit to varying degrees. This work also proposes a framework to promote renewable energy production in developing countries based on the empirical findings and existing literature. The framework highlights the leading renewable energy policy categories and specific policies most effectively promoting renewable energy production in emerging markets
A research report submitted to the Wits Business School, Faculty of Finance & Accounting, University of the Witwatersrand in partial fulfillment of the requirements for the degree of Master of Management of Finance & Investments Johannesburg 2023
Keywords: Financial Market Development; Renewable Energy; Renewable Energy Policy; Just Transition; Credit Market; Equity Market; Bond Market; UCTD; SDG-8: Decent work and economic growth; SDG-7: Affordable and clean energy